3D printing and urology: Review of the clinical applications - Wendo, K.; Olszewski, R. (Ukrainian Journal of Nephrology and Dialysis, 2020)
Three-dimensional (3D) printing is a process that translates a 3D virtual model into its physical 3D replica. In medicine, Neurosurgery, Orthopedics and Maxillo-facial surgery were the first specialties to successfully incorporate this technology in their clinical routine, as an aid to surgical interventions. The study aimed to provide a clear overview of the potential areas of applications of 3D printing (3DP) for management of renal diseases, based on a review of the literature. Method. We carried out a review of the literature according to PRISMA recommendations. We searched three databases (Medline, Scopus and Cochrane) with two specific queries: one using MeSH-terms and the second one based on free terms, all terms were related to nephrology and three-dimensional printing technology. Results. 3D-printed models were mostly employed for the management of renal tumors and lithiasis. They provided enhanced visualization of structures and the possibility to perform procedures rehearsals which seemed to improve surgical procedures. Models were also reported to positively impact patients’ understanding of their condition and the interventions. Trainees and experienced urologists also benefited from the supportive role of 3D-printed models and reported improved confidence and efficiency. Rare reports discussed their use for kidney transplantation, ureteropelvic junction obstruction syndrome treatment, nuclear medicine or cultural issues. Due to a meager data amount and heterogeneity of studies, no advanced statistical analysis was possible. Conclusion. 3D-printed models of renal anatomical structures are feasible and are valuable tools to support renal disease management, and for educational purposes.